2019
DOI: 10.37868/sei.v1i1.34
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable engineering challenges towards Industry 4.0: A comprehensive review

Abstract: This article reviews Industry 4.0, its emerging phase, implementation, challenges, benefits, etc. It combines various fields where it has any influence and leave some changes and where it require some adaptation. Papers from last 4 years are taken and analyzed, what is written about this topic in various countries with different backgrounds and economic development. Industry 4.0 affect production environment introducing new technologies which require better educated workforce so it affect education and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 74 publications
1
12
0
Order By: Relevance
“…There is a consolidation in the development of research that has led to an increase in the number of contributions, in relation to the implementation of management and implementation of sustainable policies in industrial processes. Similarly, there is an evolution in terminology that is accompanied by the emergence of new lines of research, such as those expressed below and in line with the results obtained [137,138]. Figure 7 shows the changes over time and stability of each keyword network, because we can identify the time period in which they have been studied, according to the research sample observed in the 1988-2019 period.…”
Section: Abstract Analysissupporting
confidence: 58%
“…There is a consolidation in the development of research that has led to an increase in the number of contributions, in relation to the implementation of management and implementation of sustainable policies in industrial processes. Similarly, there is an evolution in terminology that is accompanied by the emergence of new lines of research, such as those expressed below and in line with the results obtained [137,138]. Figure 7 shows the changes over time and stability of each keyword network, because we can identify the time period in which they have been studied, according to the research sample observed in the 1988-2019 period.…”
Section: Abstract Analysissupporting
confidence: 58%
“…On the other hand, preferring biking and walking are essential to public health and well-being. Accordingly, municipal authorities may invest more on personalized public transportation means, such as scooters, bikes, etc., which are empowered with new internet of things (IoT) technologies ( [31] ). Furthermore, the new hygiene perception of passengers on public transportation necessitates defining new hygiene standards by the policy makers.…”
Section: Case Study Findingsmentioning
confidence: 99%
“…For this reason, it is challenging to find new insulation materials that have good thermal properties and, at the same time that they are environmentally friendly [14]. Natural renewable insulation material can promise building applications to achieve more sustainable engineering [15] and a healthier environment. Compared to the traditional non-renewable materials, renewable materials have significantly better performances, such as less impact on global warming, longer useful lifetime [16], and lower thermal diffusivity [17].…”
Section: Introductionmentioning
confidence: 99%